THE EFFECTS OF MONETARY REWARDS FOR GRANDCHILD CARE ON THE MENTAL HEALTH OF GRANDPARENTS IN DIFFERENT INCOME CONTEXTS. (11th November 2018) - Lee, K; Jun, H; Joo, S
Abstract: The purpose of this study is to investigate the various effects of monetary reward from adult-children on the mental health of grandparents and how this differs according to income levels. For the analysis, the third wave data of the Korea Retirement and Income Study was utilized. The sample was grandparents who took care of grandchildren and who responded to the question about receiving monetary rewards for grandchild care from their adult-children. In this study, coarsened exact matching (CEM) and weighted OLS regression were applied for the analyses. All analyses were separately performed on two groups, which were divided by the level of average income (N high-income group =180, N lower-income group =203). The results showed that the effect of the receiving monetary rewards for grandchild care on grandparents' mental health was not statistically significant among the high income group but significant among the low-income group. This suggests that monetary rewards for grandchild care works differently on grandparents' mental health depending on their level of income. Particularly, the concept of reciprocity between grandchild care and monetary rewards may explain the intergenerational exchange in lower income contexts. These results also suggest that institutional support for low-income grandparents, especially, economic support from the government, may be needed. This study may be meaningful in that it dealt with the effects of monetary rewards for grandchild caring on grandparents in terms of various income contexts.